Body mass index and partial remission in 119 children with type 1 diabetes—a 6-year observational study - Sokołowska-Gadoux, Magdalena; Jarosz-Chobot, Przemysława; Polanska, Joanna; Kalemba, Alicja; Chobot, Agata (Frontiers in Endocrinology, 2023)
Background/objective This long-term study aimed to analyze the associations between BMI Z-score, HbA1c, and daily insulin requirement (DIR) and the prevalence and duration of partial remission (PR) in children and adolescents with type 1 diabetes (T1D). Methods After retrieving retrospective data for 195 patients from their health records at 24, 48, and 72 months after T1D diagnosis, the study group was comprised of 119 (57 girls) children with a complete dataset for all 6 years. PR was defined according to the ISPAD guidelines. Analyses were carried out in the whole group and subgroups according to PR duration: no PR at all (NPR), PR lasting less than 2 years (PR < 2), and PR at least 2 years (PR ≥ 2). Results PR was observed in 63% of the patients (78.9% of overweight and 100% of obese patients). NPR patients showed the lowest mean initial BMI Z-score [−0.65 ± 1.29 vs. 0.02 ± 1.42, (PR < 2), p = 0.01 and vs. 0.64 ± 1.43 (PR ≥ 2), p = 0.17]. The dissimilarity in BMI across patients declined over time. Within the NPR group, the initial mean BMI Z-score significantly increased within the first 2 years (unadjusted p < 0.001) and remained constant afterward. In the PR <2 group, the highest increase in BMI Z-score occurred after 4 years (p < 0.001) and then decreased (p = 0.04). In the PR ≥2, the BMI Z-score slightly decreased within the first 2 years (p = 0.02), then increased (p = 0.03) and remained unchanged for the last 2 years. Six years after T1D started, the mean DIRs do not differ among the patient groups (ANOVA p = 0.272). Conclusion During 6 years of follow-up, PR occurred in almost two-thirds of the studied children including almost all overweight and obese children. We observed a gradual normalization of the BMI Z-score at the end of the follow-up. BMI Z-score increased slightly in children with no remission initially but remained later constant until the end of observation. In both remitter groups, the increase in BMI Z-score appeared later when the protective honeymoon period ended. Regardless of BMI Z-score, the β-cell destruction process progresses, and after 6 years, the DIR is similar for all patients.